GAMBARAN KARAKTERISTIK DAN SOSIAL BUDAYA MASYARAKAT TERHADAP KEJADIAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS SAWIT SEBERANG KECAMATAN SAWIT SEBERANG KABUPATEN LANGKAT 2015 - shella monica; Alam Bakti Keloko; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
Abstract The characteristic feature of social culture and the incidence of hypertension is to portray the way of life of the people who looked at the behavioral manifestations of hypertensive patients.This type of research is research that is descriptive with qualitative approach using in-depth interviews (depth interview) with five informants. aims to describe the social and cultural characteristics of the community on the incidence of hypertension in Puskesmas Subdistrict Sawit Sawit Seberang Seberang Langkat 2015. Results of this study demonstrate knowledge of informants has been good enough that it can mention understanding hypertension, hypertension symptoms, prevention of hypertension and eat food that is recommended and not recommended for hypertension, alcohol consumption and smoking. Patients had an attitude supportive of hypertension occurs in the elderly, hypertension is more common in men than in women, hypertension occurs in people who work and good income, hypertension as a hereditary disease. Action informants have eating habits that are less well because they consume foods that are not recommended for patients with hypertension, still smoking and drinking coffee